Coevolutionary analysis of Appalachian Xystodesmid millipedes and their symbiotic Mesostigmatid mites - Swafford, Angela Lynn (East Carolina University, 2010)
Mites (Acari) form symbiotic relationships with many animal taxa including fish, amphibians, reptiles, birds, mammals, mollusks, and arthropods. They are frequently found living on millipedes, and it has often been speculated that these two groups of arthropods have, in some cases, undergone coevolution. However, this hypothesis has never been formally tested. Millipedes of the family Xystodesmidae Cook, 1985 (Diplopoda: Polydesmida) are often host to several symbiotic mite species, but very little work has been done to identify these acarines or to understand their relationship to the millipedes. In an attempt to better understand these associations, mites and their xystodesmid millipede hosts were collected in the broadleaf forests of the eastern United States. Mites in the genera Stylochyrus Canestrini and Canestrini, 1882 (Mesostigmata: Ologamasidae) and Schwiebea Oudemans, 1916 (Sarcoptiformes: Acaridae) were very prevalent among millipedes in the genera Apheloria Chamberlin, 1921; Appalachioria Marek and Bond, 2009; Boraria Chamberlin, 1943; Brachoria Chamberlin, 1939; Dixioria Chamberlin, 1947; Nannaria Chamberlin, 1918; Pleuroloma Rafinesque, 1820; Prionogonus Shelley, 1982; Rudiloria Causey, 1955; and Sigmoria Chamberlin, 1939. Of the mite taxa collected, the species Stylochyrus rarior (Berlese, 1916) was found on the greatest number of sampled millipede taxa. The complete mitochondrial genome of S. rarior associated with an individual of the millipede genus Apheloria (Polydesmida: Xystodesmidae) was sequenced. The genome is 14,900 nucleotides in length, has all the typical genes of an arthropod mitochondrion, differs in gene arrangement from that of the ancestral arthropod, and has a gene order that is unique among mites and ticks. The major difference in S. rarior is the placement of the protein-coding gene nad1, which is positioned between the ribosomal RNA gene 12S and the protein-coding gene nad2 (transfer RNA genes and non-coding regions excluded). For use in coevolutionary analyses, the DNA from two mitochondrial regions (16S/12S and cox1) was sequenced for all collected xystodesmid millipede and Stylochyrus mite specimens. Phylogenetic trees were reconstructed for both of these millipede and mite taxa using Bayesian inference. Pairwise distance data was used in distance-based coevolutionary analyses, and reconstructed phylogenies were used in tree-based coevolutionary analyses. The phylogenetic analyses indicate Stylochyrus and xystodesmid millipede evolutionary history is incongruent. Moreover, the evolutionary relationships among mite individuals and populations have very low support values and indicate little to no geographic structuring. The coevolutionary analyses likewise detected no pattern of coevolution among these millipede and mite lineages. Unlike many arthropod species, Stylochyrus mites appear to be highly vagile.
Keywords: Biology; Coevolution--Research; Symbiosis--Research; Xystodesmidae; Parasitiformes; Nucleotide sequence